A REVIEW ON FTIR SPECTROSCOPIC ANALYSIS - Bhadoria, Suraj Singh; H Venkatesan; G S Chakraborty (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article examines some of the most recent developments in FTIR spectroscopy in fields pertaining to cell biology and natural tissues. It outlines some of the most popular peak frequencies and their assignments and is the second review article that came from an extensive investigation into the use of spectroscopic technologies in biological studies. By incorporating the majority of the significant peaks seen in natural tissues, these investigations seek to create a library of molecular fingerprints that will aid researchers in determining the chemical structure of biological tissues. There appears to be a significant resemblance in determining the peaks of identical sections of the FTIR spectra despite the use of different techniques. Therefore, it is thought that creating a distinctive collection